Allylamino diphenylphosphine oxide and poss containing flame retardant photocured hybrid coatings - ÇAKMAKÇI, EMRAH (ELSEVIER SCIENCE SA, 2017)
In this work the synergistic effect of a nitrogen and phosphorus containing reactive monomer; allylamino diphenylphosphine oxide (AADPPO or allyl phosphinic amide-APA) and octamercaptopropyl polyhedral oligomeric silsesquioxane (POSS-8SH) on the flame retardancy of photocured epoxy acrylate based coatings was investigated. The incorporation of APA into an epoxy acrylate decreased the gel contents and the double bond conversions. On the other hand the addition of POSS-8SH significantly increased the double bond conversions. Mechanical properties were significantly affected from the degree of cure. Tensile strength of the coatings decreased as the amount of the monofunctional APA was increased. Flammability of the photocured hybrid coatings was determined by the limiting oxygen index (LOI) and UL94 tests. Flame retardancy of the epoxy acrylate was increased with the addition of APA but decreased with the addition of POSS. 20 wt.% APA containing coatings showed a LOI value of 27 but they failed to pass the UL94 test. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Flame retardant; Phosphorus; Nitrogen; POSS; Photocurable coatings; POLYHEDRAL OLIGOMERIC SILSESQUIOXANE; CURING EPOXY ACRYLATE; THERMAL-DEGRADATION; DOPO-POSS; COORDINATION CHEMISTRY; MECHANICAL-PROPERTIES; PHYSICAL-PROPERTIES; COMPOSITES; PHOSPHORUS; NANOCOMPOSITES